Renewable Energy Sources (RES): An Overview with Indian Context (International Journal of Engineering and Computer Science, 2014)
Nowadays Renewable Energy Sources (RES) play an important role in electricity market as the changing climate is placing our planet in peril .So, there is an urgent need for transition from existing fossil fuel based energy system to one based on Renewable Energy Sources(RES) to decrease dependence on  depleting reserves of fossil fuels with an objective to assess how Sustainable Development is possible. This paper  presents an overview of various renewable energy sources such as solar power, wind power, small hydro power(SHP), Biomass Power(BP), Geothermal Power(GP), Tidal Power(TP), Ocean Thermal Energy Conversion(OTEC), hydrogen fuel cell etc .This paper comprehensively elucidates why we are going towards RES ,their economic, social  and environmental impact, challenges associated with RES  and also suggests some recommendations in order to promote RES  to ensure  Sustainable Development.